2016
DOI: 10.1002/ldr.2508
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Astragalus adsurgens Roots and Canopy to Water Erosion Control in the Water–Wind Crisscrossed Erosion Region of the Loess Plateau, China

Abstract: Simulated rainfall experiments were conducted to investigate the effect of Astragalus adsurgens roots and canopy on water erosion yield, erosion processes and soil resistance to erosion. Experiments were conducted on grass, root and bare slopes, with sandy soil from a water–wind crisscrossed erosion region of the Loess Plateau, China. A. adsurgens coverage on grass slopes was approximately 40%. There were three rainfall intensities of 30, 60 and 90 mm h–1 and four slope gradients of 3, 6, 9 and 12°. A. adsurge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 61 publications
5
36
0
Order By: Relevance
“…With regard to erosion, the authors state that the mulch had a greater protective effect on the soil compared to the canopy, while the combined effect decreased erosion by 99% compared to the bare soil. The roots also helped to reduce soil erosion [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to erosion, the authors state that the mulch had a greater protective effect on the soil compared to the canopy, while the combined effect decreased erosion by 99% compared to the bare soil. The roots also helped to reduce soil erosion [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Molina et al () showed that sediment yield decreased exponentially with an increasing vegetation cover in a central Andean mountain area, the lithology also influenced the catchment sediment yield significantly and explained an additional 23% of the observed variance in specific sediment yield. Grassland showed the highest values in soil quality properties, and soil loss was reduced by 70% on slopes with the grass compared with bare slopes in water–wind crisscrossed erosion regions of the Loess Plateau (Zhao et al , ; Zhao et al , ). The land use changes alone reduced sediment yield up to 14%, but in combination with check dams, the reduction in sediment yield reached 44 ± 6% in southeast of Spain (Quiñonero‐Rubio et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation restoration improves soil resistance to concentrated flow erosion mainly through the combined effects of root system and soil properties (Zhou and Shangguan, 2008;Zhang et al, 2014;Zhao et al, 2016). In terms of root system, plant roots can enhance the soil structure, soil shear strength, and soil infiltration capacity and thus improve soil resistance to flow erosion (Gyssels and Poesen, 2003;De Baets et al, 2006Vannoppen et al, 2015;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%